2003
DOI: 10.2165/00128072-200305030-00001
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Hypothyroidism

Abstract: Because thyroid hormone is essential for normal brain development, children born with congenital hypothyroidism who lack thyroid hormone during a circumscribed period of early development are at risk of brain damage and mental retardation. Since the advent of newborn screening programs in the 1980s, the diagnosis and treatment of this condition are now provided in the first 2-3 weeks of birth in most regions. While this is usually sufficient to prevent mental retardation, the children so identified attain mild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(9 citation statements)
references
References 98 publications
(94 reference statements)
0
9
0
Order By: Relevance
“…A recent study with an animal model of schizophrenia (Li et al, 2007) showed that a brief induction of a DISC1 mutant allele during postnatal development, but not in adults, is sufficient to trigger many of the phenotypes associated with this neurodevelopmental disorder (Weinberger, 1987). Clinical experience with endocrine and metabolic disorders also stresses the importance of insults during vulnerable periods of development: hypothyroidism and phenylketonuria, for example, can lead to profound and irreversible cognitive disability when left uncorrected during developmental periods, while they appear to have milder effects in adults (Davis and Tremont, 2007; Dugbartey, 1998; Hanley, 2004; Rovet and Daneman, 2003; Zoeller and Rovet, 2004). Nevertheless, there are many other examples of pathologies where the opposite is true: for example, trauma, infection, and ischemia may have much of the same or even more dire effects in adults than in developing organisms (Kolb et al, 2000; Vannucci and Hagberg, 2004).…”
Section: The Traditional Viewmentioning
confidence: 99%
“…A recent study with an animal model of schizophrenia (Li et al, 2007) showed that a brief induction of a DISC1 mutant allele during postnatal development, but not in adults, is sufficient to trigger many of the phenotypes associated with this neurodevelopmental disorder (Weinberger, 1987). Clinical experience with endocrine and metabolic disorders also stresses the importance of insults during vulnerable periods of development: hypothyroidism and phenylketonuria, for example, can lead to profound and irreversible cognitive disability when left uncorrected during developmental periods, while they appear to have milder effects in adults (Davis and Tremont, 2007; Dugbartey, 1998; Hanley, 2004; Rovet and Daneman, 2003; Zoeller and Rovet, 2004). Nevertheless, there are many other examples of pathologies where the opposite is true: for example, trauma, infection, and ischemia may have much of the same or even more dire effects in adults than in developing organisms (Kolb et al, 2000; Vannucci and Hagberg, 2004).…”
Section: The Traditional Viewmentioning
confidence: 99%
“…For example, mutations leading to phenylketonuria have serious effects during development, but stopping treatment results only in mild phenotypes in adults [2]. Similarly, untreated congenital hypothyroidism can lead to profound and irreversible cognitive deficits, while hypothyroidism in adults has milder effects on cognitive function [3–6]. Although development may be an especially fragile period, there are also examples of manipulations that result in far more serious effects in adults than in development.…”
Section: The Long-term Impact Of Disrupting Neurodevelopmental Processesmentioning
confidence: 99%
“…Numerous studies have shown that CH screening enables normal progression of cognitive development with early diagnosis and treatment in children with severe CH and the time to normalization of thyroid hormones affects developmental outcomes (20-22). On the other hand, it was observed that a notable developmental negativity did not ocur in mild or subclinical (diagnosed only with moderately elevated TSH) hypothyroidism when studies evaluating developmental outcomes of screening were reviewed.…”
Section: Neonatal Congenital Hypothyroidism; the Approach To Babiementioning
confidence: 99%